“O que tenho a comemorar? o que foi que eu fiz da minha vida? ” : a saúde mental de professores da educação básica de Garanhuns-PE - Ramos, Mylena Carla Almeida Tenório (2018)
The present work presents a research carried out in the municipal network of Garanhuns / Pernambuco, which aimed to understand the mental health of the teacher who works in the initial years of Elementary School. The specific objectives were to map Garanhuns' municipal education network in relation to the inclusion of students with disabilities, as well as the profile of a group of teachers of the network, and to analyze how this professional has experienced inclusion in terms of his mental health , aiming to highlight the situations and factors that contribute to the emergence of suffering in the exercise of the teaching profession in the process of school inclusion. In this way, we start from the trinomial health, work and education, through the increasing increase of studies related to this subject, also following the assumption of Clot (2010), in which the clinic of the activity starts to be used in a search for work analysis and its development, in order to rekindle the workers' power to act, either individually or collectively. It is a mixed research with a quali-quanti approach. The following instruments were used to produce data: questionnaire with quantitative and qualitative questions for mapping aspects related to participants' health, carried out in three municipal schools with the largest number of students included, with 21 teachers participating. Then, it was proposed a photo production of situations considered to cause the sickness of these professionals in the work environment, carried out in one of the schools of the network, which has an ESA room, with 3 teachers. A group interview was conducted of the situations recorded, which represent situations of distress, pain or pleasure. From the analysis by descriptive statistics and starting from the created categories, we verified that the aggravating of the health of these teachers is something present, independent of the inclusion process, and the environment itself causes anguish and suffering. The results pointed to teachers' dissatisfaction, given the lack of training, physical structure and support of the competent bodies, as well as poor pay and working conditions.